1998
DOI: 10.1046/j.1369-6513.1998.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a patient decision aid for choice of surgical treatment for breast cancer

Abstract: Purpose A patient decision aid for the surgical treatment of early stage breast cancer was developed and evaluated. The rationale for its development was the knowledge that breast conserving therapy (lumpectomy followed by breast radiation) and mastectomy produce equivalent outcomes, and the current general agreement that the decision for the type of surgery should rest with the patient. Methods A decision aid was developed and evaluated in sequential pilot studies of 18 and 10 women with newly diagnosed breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
35
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 50 publications
2
35
0
1
Order By: Relevance
“…Variance constriction because of a ceiling effect may have contributed to the lack of a group difference. Results are in line with other studies, which reported null effects of decision aids on satisfaction judgements (Sawka et al, 1998;Whelan et al, 1999), whereas some studies demonstrated short (Whelan et al, 2004) or long-term effects (Molenaar et al, 2001). Discrepant findings may be related to individual differences in cognitive processing of the decision making phase on which the decision aids also have an impact.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Variance constriction because of a ceiling effect may have contributed to the lack of a group difference. Results are in line with other studies, which reported null effects of decision aids on satisfaction judgements (Sawka et al, 1998;Whelan et al, 1999), whereas some studies demonstrated short (Whelan et al, 2004) or long-term effects (Molenaar et al, 2001). Discrepant findings may be related to individual differences in cognitive processing of the decision making phase on which the decision aids also have an impact.…”
Section: Discussionsupporting
confidence: 88%
“…However, on the 'information' subscale of the decisional conflict scale which is considered as one of two indicators of decision quality (O'Connor et al, 2003), patients who underwent the decision aid intervention reported feeling better informed than participants in the control arm. Effects on informational levels have been also shown in other studies in women with newly diagnosed breast cancer (Sawka et al, 1998;Whelan et al, 2003Whelan et al, , 2004.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Sawka et 1 Choice between lumpectomy with radiation and mastectomy al. 109,110 for early breast cancer. Schapira et al 111 1…”
mentioning
confidence: 99%